Causal relationship between physical activity and platelet traits: a Mendelian randomization study - Jia, Mingyuan; Wang, Zhiyong; Hu, Fengting (Frontiers in Physiology, 2024)
This study used a two-sample Mendelian randomization method to explore the causal relation between different types of physical activity and platelet traits. The sample data for the study were obtained from the European Large Scale Physical Activity dataset (N=460,376) and the Platelet Trias dataset (N=350,474). The causal effects were estimated using inverse variance weighting, MR-Egger, and weighted median.Sensitivity analyses were performed using Cochran's Q test, funnel plot, and leave-oneout analysis. The results showed that light DIY, other exercises, strenuous sports, and walking for pleasure were associated with decreased platelet counts. Still, none of the heavy/light DIY was associated with increased platelet counts. There was no causative relationship existed between the type of physical activity explored and the mean platelet volume and platelet distribution widths in this study. Our study results support the causal relation between partial types of physical activity with platelet counts and mean platelet volume. Therefore, it is essential to consider the impact of relevant physical activity on platelet traits when noticing their abnormal physiologic indices.